Power-discourse Relationship in a Croatian Higher Education Setting - Renata Fox; John Fox (Education Policy Analysis Archives, 2002)
Croatian higher education system's public space is researched through a critical analysis of a Croatian faculty's discourse. Representing a typical faculty social situation, two council meetings— recorded in minutes—are critiqued. Both meetings' minutes provide evidence of discourse strategies of deception used by faculty power holders to create an illusion of consent. We attribute the success of the deception to council members' ideas about the Faculty's groups/individuals, relations and issues related to the Faculty's hierarchy, their rank within that hierarchy, and their position within the Faculty's social network. To support our argument, we explore how the Faculty power holders' discourse is built on a power/ideology/language formation. We conclude that, failing to critique the faculty's discourse, council members neglected their historical task of paving the way to democracy.